Analisis Pengaruh Faktor Internal Dan Faktor Eksternal Terhadap Non Performing Financing (NPF) Pada Bank Umum Syariah Di Indonesia - Fatimah, Natasyanurul; Izzaty, Khairina Nur (Journal Of Islamic Economics And Finance, 2022)
This study aims to analyze the influence of internal factors such as FDR, CAR, and BOPO as well as external factors such as inflation, BI rate, and exchange rates against Non Performing Financing (NPF) at Islamic Commercial Banks in Indonesia. This study uses a quantitative approach carried out at Islamic Commercial Banks registered with the OJK in the first quarter of 2019 to the third quarter of 2021, with the use of secondary data based on times series in the form of quarterly. The sample in this study was determined using a purposive sampling method so that 9 Islamic Commercial Banks were obtained according to the criteria. The data analysis method used is multiple linear regression and goodness of fit test of a model that is processed using IBM SPSS 25. Based on the results of data testing shows that: (1) Financial to Deposit Ratio (FDR) has no significant effect on Non Performing Financing (NPF), (2) Capital Adequacy Ratio (CAR) has no significant effect on Non Performing Financing (NPF), (3) Operating Expenses on Operating Income (BOPO) has a positive and significant effect on Non Performing Financing (NPF), (4) inflation does not have a significant effect on Non Performing Financing (NPF), (5) the BI rate does not significantly affect Non Performing Financing (NPF), (6) the exchange rate has a positive and significant effect on Non Performing Financing (NPF).